The Utilization of Language Styles by the Characters in the Movie Oppenheimer - Anak Agung Gde Bagus Rama Putra; I Gusti Ayu Gde Sosiowati; I Gusti Ayu Mahatma Agung (FKIP, Universitas Palangka Raya, 2025)
This article aims to identify the types of language styles utilized by the characters as well as to analyze the factors that influence its utilization in the movie Oppenheimer through the application of Joos’ (1967) types of language styles theory and Holmes’ (2013) social factors and dimensions theory. This article employed a qualitative method to analyze both the types of language styles and the factors that influence the characters to utilize different types of language styles in the movie Oppenheimer. In collecting the data, this article employed a documentation method and a note-taking technique. In analyzing the data, this article employed a descriptive qualitative method to ensure a detailed and thorough analysis of the data. In presenting the analysis, a descriptive qualitative method was employed to present the data thoroughly by using words and sentences. Based on the findings, the characters in the movie Oppenheimer utilized all types of language styles, which include frozen style, formal style, consultative style, casual style, and intimate style. Moreover, there are four main components that influence the characters to utilize different types of language styles, namely, participants, setting, topic, and function.